Interleukin 17A Participates in Renal Inflammation Associated to Experimental and Human Hypertension - Orejudo, Macarena; Rodrigues-Diez, Raul R.; Rodrigues-Diez, Raquel; Garcia-Redondo, Ana; Santos-Sánchez, Laura; Rández-Garbayo, Javier; Cannata-Ortiz, Pablo; Ramos, Adrian M.; Ortiz, Alberto; Selgas, Rafael; Mezzano, Sergio; Lavoz, Carolina; et al. (Frontiers in Pharmacology, 2019)
Hypertension is now considered as an inflammatory disease and the kidney is a key end-organ target. Experimental and clinical studies suggest that IL-17A is a promising therapeutic target in immune and chronic inflammatory diseases, including hypertension and kidney disease. Elevated circulating IL-17A levels have been observed in hypertensive patients. Our aim was to investigate whether chronically elevated circulating IL-17A levels could contribute to kidney damage, using a murine model of systemic IL-17A administration. Blood pressure increased after 14 days of IL-17A-infusion in mice when compared to control mice, and this was associated to kidney infiltration by inflammatory cells, including CD3+ and CD4+ lymphocytes and neutrophils. Moreover, proinflammatory factors and inflammatory-related intracellular mechanisms were upregulated in kidneys from IL-17A-infused mice. In line with these findings, in the model of Angiotensin II infusion in mice, IL-17A blockade, using an anti-IL17A neutralizing antibody, reduced kidney inflammatory cell infiltrates and chemokine overexpression. In kidney biopsies from patients with hypertensive nephroesclerosis IL-17A positive cells, mainly Th17 and γδ T lymphocytes, were found. Overall, the results support a pathogenic role of IL-17A in hypertensive kidney disease-associated inflammation. Therapeutic approaches targeting this cytokine should be explored to prevent hypertension-induced kidney injury.